NAMA TOKO DAN IKLAN TIKTOK UNTUK MENARIK KONSUMEN MENGUNJUNGI DESA ANJUN PLERED - Innas Rovino Katuruni; Tetty Rimenda; Agus Buntoro; R. Elly Mirati (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2023)
Community Service Activities help ceramic craftsmen and entrepreneurs selling ceramics in the village of Anjun Plered, Purwarkarta. Since the pandemic period, visitors have decreased as a result of ceramic craftsmen and entrepreneurs who have been forced to close their businesses. Data collection was done by observation and interviews. After the problems are identified, activities are designed using a pull marketing strategy to overcome the decline in visitors. The program (1) Puts up names in ceramic selling shops. Name function to distinguish from other stores. With an eye-catching signage, consumers are hooked on their eyes to stop by the shop. There are 4 shop signboards installed on the main street of Anjun village, namely Hana Keramik, Saluyu Keramik, Bibilintik and Cupumanik. To strengthen the pull effect, the marketing strategy was designed for promotional videos about shops selling ceramic products. Videos are uploaded to social media using the TikTok application. There are three videos that have been uploaded to the Tiktok application http://www.tiktok.com/@pengmaskbk_bkt.